Elemental analysis of tree leaves by total reflection X-ray fluorescence: New approaches for air quality monitoring. (July 2017) - Bilo, Fabjola; Borgese, Laura; Dalipi, Rogerta; Zacco, Annalisa; Federici, Stefania; Masperi, Matteo; Leonesio, Paolo; Bontempi, Elza; Depero, Laura E.
Abstract: This work shows that total reflection X-ray fluorescence (TXRF) is a fast, easy and successful tool to determine the presence of potentially toxic elements in atmospheric aerosols precipitations on tree leaves. Leaves are collected in eleven parks of different geographical areas of the Brescia city, Northern Italy, for environmental monitoring purposes. Two sample preparation procedures are considered: microwave acid digestion and the novel SMART STORE method for direct analysis. The latter consists in sandwiching a portion of the leaf between two organic foils, metals free, to save it from contamination and material loss. Mass composition of macro, micro and trace elements is calculated for digested samples, while relative elemental amount are obtained from direct analysis. Washed and unwashed leaves have a different composition in terms of trace elements. Differentiation occurs according to Fe, Pb and Cu contributions, considered as most representative of air depositions, and probably related to anthropogenic sources. Direct analysis is more representative of the composition of air precipitations. Advantages and drawbacks of the presented methods of sample preparation and TXRF analysis are discussed. Results demonstrate that TXRF allows to perform accurate and precise quantitative analysis of digested samples. In addition, direct analysis of leaves may be used as a fast and simple method for screening in the nanograms range. Graphical abstract: Highlights: Elemental analysis of tree leaves is performed for air quality monitoring. TXRF analysis is performed on leaves from 6 tree species and 11 urban parks. Metals from anthropogenic sources contribute to differentiation of washed and unwashed samples. The novel SMART STORE method for sample preparation allows direct TXRF analysis. Advantages of the two sample preparation procedures are presented and discussed.